163k views
0 votes
Plz help me and I will give you lot of points

Plz help me and I will give you lot of points-example-1
User Wenlong
by
4.5k points

2 Answers

5 votes

Answer:

Step-by-step explanation:

its fliped i cant see

User Ppolv
by
5.0k points
7 votes

Answer:

t = - 3, t = - 1

Explanation:

Given

h(t) = t² + 4t + 3

To find the zeros equate h(t) to zero, that is

t² + 4t + 3 = 0

Consider the factors of the constant term (+ 3) which sum to give the coefficient of the t- term

The factors are + 3 and + 1, since

3 × 1 = 3 and 3 + 1 = 4, thus

t² + 4t + 3 = (t + 3)(t + 1) = 0

Equate each factor to 0 and solve for t

t + 3 = 0 ⇒ t = - 3

t + 1 = 0 ⇒ t = - 1

smaller zero is t = - 3

larger zero is t = - 1

HOPE THIS IS THE ANSWER YOU WERE LOOKING FOR

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.